An Active Inference Approach to Interoceptive Psychopathology - Paulus, Martin P; Feinstein, Justin S; Khalsa, Sahib S (Annual review of clinical psychology, 2019)
Interoception refers to the process by which the nervous system senses and integrates signals originating from within the body, providing a momentary mapping of the body's internal landscape and its relationship to the outside world. Active inference is based on the premise that afferent sensory input to the brain is constantly shaped and modified by prior expectations. In this review we propose that interoceptive psychopathology results from two primary interoceptive dysfunctions: First, individuals have abnormally strong expectations of the situations that elicit bodily change (i.e., hyperprecise priors), and second, they have great difficulty adjusting these expectations when the environment changes (i.e., context rigidity). Here we discuss how these dysfunctions potentially manifest in mental illness and how interventions aimed at altering interoceptive processing can help the brain create a more realistic model of its internal state.